Rationalizability in Games with a Continuum of Players - Jara-Moroni, P (2012)
The concept of rationalizability has been used in the last fifteen years to study stability of equilibria in models with a continuum of agents such as competitive markets, macroeconomic dynamics and currency attacks. However, rationalizability has been formally defined in general settings only for games with a finite number of players. We propose an exploration of rationalizability in the context of games with a continuum of players. We deal with a special class of these games, in which payoff of each player depends only on his own strategy and on an aggregate value: the state of the game, which is obtained from the complete action profile. We define the sets of point-rationalizable states and rationalizable states. For the case of continuous payoffs and compact strategy sets, we characterize these sets and prove their convexity and compactness. We provide as well results on the equivalence of point- and standard-rationalizability. © 2012 Elsevier Inc.